2008
DOI: 10.2139/ssrn.1033436
|View full text |Cite
|
Sign up to set email alerts
|

Are Flexible Contracts Bad for Workers? Evidence from Job Satisfaction Data

Abstract: If workers can choose between permanent and flexible contracts, compensating wage differentials should arise to equalize on-the-job utility in the two types of contracts. Estimating job satisfaction using the British Household Panel Survey shows that agency and casual contracts are associated with routinely lower satisfaction. This results because the low job satisfaction associated with less job security is not offset by higher compensation or other job characteristics. Job security is sufficiently important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We observe that casuals are less satisfied with their jobs than permanent workers, the omitted category. Green and Heywood (2007) In Columns 3 and 5 we split contract status by hours worked, using a similar classification to that used by Wooden and Warren (2004). The omitted case is permanent employees who work a standard week (35-39 hours); a `standard' employment contract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe that casuals are less satisfied with their jobs than permanent workers, the omitted category. Green and Heywood (2007) In Columns 3 and 5 we split contract status by hours worked, using a similar classification to that used by Wooden and Warren (2004). The omitted case is permanent employees who work a standard week (35-39 hours); a `standard' employment contract.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research into flexible employment has tended to focus on either subjective evaluations of worker well being, such as responses to job satisfaction questions (Bardasi and Francesconi 2004;Green and Heywood 2007;Ferrer-i-Carbonell and Van Praag 2006;Kaiser 2002) or objective evaluations, such as access to training (Arulampalam and Booth 1998;Draca and Green 2004), relative rates of pay (Morreti 2000) or the effect on the likelihood of gaining permanent employment (Green and Leeves 2004;Guell and Petrongolo 2000). Few studies have investigated both objective and subjective evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies confirm the detrimental impact of flexible contracts. Some find negative effects of temporary work on job satisfaction which are linked to perceived job insecurity and involuntariness (Origo & Pagani, 2006;Green & Heywood, 2007). Similar findings, using the European Community Household Panel Survey data, state lower levels of overall satisfaction for fixed-term full-time workers and the self-employed (Kaiser, 2002).…”
Section: Introductionmentioning
confidence: 78%
“…For instance, research on the aspects that define a good job emphasises the importance of taking into account a large variety of employee-desirable job factors, most of which can be described as related to WFPs, such as hours of work or job security (Barting et al, 2012;Clark, 1998;Jones et al, 2012;Origo and Pagani, 2008;Petrescu and Simmons, 2008). In fact, in a large-scale study in Britain, job security is found to be a key desirable factor, to the extent that, if job security were the same, differences in job satisfaction would be expected to be eliminated between employees on permanent and non-permanent types of contract (Green and Heywood, 2007). Table 4 show that, compared to the number of forty EEA migrants hired by the average British workplace, there are likely to be six more EEA workers in workplaces implementing job security, two more EEA workers if implementing Working from home, three more EEA workers if the workplace provides a nursery as part of its family policies, three more EEA workers if pay is contingent on results, one more EEA workers if Training is provided or Teamwork is used, and nearly one fewer employees if offering relatively low pay.…”
Section: Econometric Model Methods and Testingmentioning
confidence: 99%